The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1177/17298814211012325
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 3-RRR Spherical Parallel Instrument for Daily Living Emulation (SPINDLE) for Functional Rehabilitation of Patients with Stroke

Abstract: Various robotic rehabilitation devices have been developed for acute stroke patients to ease therapist’s efforts and provide high-intensity training, which resulted in improved strength and functional recovery of patients; however, these improvements did not always transfer to the performance of activities of daily living (ADLs). This is because previous robotic training focuses on the proximal joints or training with exoskeleton-type devices, which do not reflect how humans interact with the environment. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…So far, most studies have focused on the kinematic issues of RSPMs, while quite a few have referred to the dynamic control of these robots. For RSPMs, several studies have been reported on a variety of relevant problems, which include modeling of workspace in joint and Cartesian space [14][15][16][17], inverse and forward kinematic analysis to obtain analytically unique real-time solutions [18][19][20][21][22][23][24][25], design and optimization [26][27][28][29][30][31][32], design and robustness [33], singularity analysis, and derivation of Jacobian matrices [34,35]. However, the constrained kinematic analysis has gone unnoticed in the literature.…”
Section: Mathematical Modeling Challenges and Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most studies have focused on the kinematic issues of RSPMs, while quite a few have referred to the dynamic control of these robots. For RSPMs, several studies have been reported on a variety of relevant problems, which include modeling of workspace in joint and Cartesian space [14][15][16][17], inverse and forward kinematic analysis to obtain analytically unique real-time solutions [18][19][20][21][22][23][24][25], design and optimization [26][27][28][29][30][31][32], design and robustness [33], singularity analysis, and derivation of Jacobian matrices [34,35]. However, the constrained kinematic analysis has gone unnoticed in the literature.…”
Section: Mathematical Modeling Challenges and Control Strategiesmentioning
confidence: 99%
“…Now, by replacing Eqs. ( 25) and (26) in Eq. ( 32), the closed-form dynamic formulation for the manipulator in the Cartesian space is obtained as follows:…”
Section: Explicit Dynamics In Task Spacementioning
confidence: 99%
“…Some ankle rehabilitation devices proposed have the 3-RRR [34], 2-RRR/UPRR [35], 2-UPS/RRR [36], 3-RRS [37] geometries and to fit more closely the ankle motion Zhang et al exploited a more complex parallel geometry [38]. There are, also, parallel geometries exploited for upper limb, wrist rehabilitation devices as those proposed in [39,40].…”
Section: Description Of the Systemmentioning
confidence: 99%
“…As an ADL robotic trainer, we developed a parallel manipulator, SPINDLE (Spherical Parallel INstrument for Daily Living Emulation), shown in Fig. 2, that allows three-dimensional rotations with a wide range of motion [43], [44]. ADL tasks in SPINDLE were designed for the participant to position SPINDLE in a particular end posture to practice both reaching and precision tasks.…”
Section: Introductionmentioning
confidence: 99%